Factors of Satisfaction with Wages of Employees of Enterprises of Stavropol Territory - Anatolyevna Ivashova, Valentina; Nikholayevna Bulankina, Nadezhda; Rashitovna Baicherova, Anzhelika; Fyodorovna Maslova, Lyubov; Vasilyevna Skrebtsova, Tamara (International Journal of Engineering and Technology, 2018)
The article considers the results of the survey reflecting the satisfaction with the remuneration of employees of enterprises of Stavropol Territory. It has been established that the issues of remuneration hold the first place in the system of assessment of the attractiveness of the workplace.In the course of factor analysis of the attractiveness of the workplace for all categories of employees, except for managers, it is found that the leading factor is the additional financial compensation received essentially through a set of social guarantees for employees of specific enterprises and organizations.The low assessment of the factors of the company's performance (increase in sales of products and services; introduction of new systems of remuneration of labor; transition to new equipment, technology and reduction of total costs for the production of goods and services), which have an impact on the increase in wages, analysis of working situations as a whole showed that the issues of improving the remuneration system remain a lever not used enough at the moment.Â